(untitled) (Innovaciones Educativas, 2025)
The main objective of this essay is to discuss the relevance of phenomenology in education and educational research. It also explores how phenomenology could be applied within the curriculum and addresses some common misunderstandings regarding the phenomenological method as well as the challenges it poses in educational settings. This work defends the following thesis: phenomenology, when applied as a philosophical approach to education and curriculum, enhances teaching and learning processes and should be taken into account across various domains, including educational research. Despite its potential, phenomenology has at times been misinterpreted throughout history, leading to disagreements and difficulties. Fermoso (1988) outlines key steps of the phenomenological method, including the suspension of judgment, description, and the understanding of essences. Meanwhile, Ayala emphasizes the interpretation of essence through lived experience. This essay concludes that phenomenology is highly significant in the field of education as it invites a reflective gaze inward through the lens of experience, while also acknowledging others. The paper also highlights challenges, such as the failure to grasp this philosophical approach, which suggests that discussions on the topic remain open. Finally, it proposes steps for documenting these experiences within educational contexts.